Impact of geopolitical risk on working capital management in companies listed on the Indonesia Stock Exchange (IDX) - Handry, Handry; Sung Suk, Kim (Enrichment : Journal of Management, 2023)
This research aims to test whether geopolitical risk affects the working capital of company management in Indonesia. By using panel data analysis, a total of 585 companies listed on the Indonesia Stock Exchange (BEI) were used as research objects. 4,044 data points were observed during the period 2013–2022 to analyze the influence of GPR (geological risk) on working capital management from three account approaches. Accounts Receivable, Accounts Payable, and Net Working Capital results show that when geopolitical tensions increase, this has a significant effect on the company's net working capital but does not have a significant impact on Accounts Receivable and Accounts Payable. Further studies are still needed to determine the extent to which geopolitical risks have an impact on company performance, especially working capital management. It is hoped that this research will be useful for policymakers to anticipate appropriate regulations in the future to help entrepreneurs and the country's economic growth. For practitioners, namely companies, business owners, and entrepreneurs, this research is expected to provide important information regarding the impact of geopolitical risk on companies, especially working capital management